A preliminary study for the establishment of a reference interval for vitamin B12 in China after performance verification of a second‐generation ECLIA kit. Issue 5 (6th January 2020) - Jiang, Wencan; Men, Shasha; wen, Xinyu; Yuan, Xiaozhou; Pu, Danna; Liu, Xiaoting; Jia, Xingwang; Wang, Chengbin
Abstract: Background: The second‐generation electrochemiluminescence immunoassay (ECLIA) kit of vitamin B12 is widely used in clinical laboratories, and the establishment of a reference interval (RI) is essential to provide the basis for clinical monitoring. The purpose of this study was to establish a laboratory RI for vitamin B12 in China and at the same time verify the method performance of the second‐generation kit. Methods: The verification of the method performance was conducted according to the Clinical and Laboratory Standards Institute (CLSI) guidelines. Based on these guidelines, a total of 580 serum samples were collected, and 391 serum samples were used for the establishment of the RI according to CLSI guidelines. The subjects were grouped by sex and age. The age groups were as follows: 21‐40, 41‐60, and 61‐80 years. The RI was defined by nonparametric 2.5th and 97.5th percentile intervals. Results: The performance of the second‐generation kit of vitamin B12 from the Roche Cobas E602 system was in compliance with laboratory requirements. Serum vitamin B12 levels conformed to a non‐Gaussian distribution. Harris‐Boyd's test did not indicate partitioning for different age and gender group. Besides, there was no significant difference between different age groups ( P  = .07) and gender groups ( P  = .2002). The RI for healthy Chinese adults (aged 21‐80 years) calculated by the nonparametric method was 250.8‐957.1 pg/mL. Conclusions: The reference range of vitamin B12 was established, which provided a theoretical basis for the clinical application and monitoring of vitamin B12 detection.